Mural As a Form of Service for Students of The UMTAS KKNT Group 13 At MI Nurul Huda, Cikembang Hill, Cimerak District - Pratama, Rayhan Bintang; Diana, Shovi; Ayu, Seni Ratna; Nur, Asty Puspita; Mulyani, Riska; Kartini, Intan Ajeng; Khotami Rahmawati, Yevi Tri; Baety, Khoerun Nisa Nur; Ningsih, Rahmayanti; Maulida, Dini; Taswin, Agung Nugraha; Noor, Iqbal Muhammad; Mahpud, Eza Sahal; Hendrawan, Budi (AbdimasMu UMTAS, 2025)
In implementing the GLS program, community service activities were carried out in Cikijing Hamlet and Cijaringao Hamlet, Sindangsari Village, Cimerak District, Pangandaran Regency which were carried out for 32 days starting from August 8 to September 8 2022. The target of this program is SDN 3 Sindangsari which located in Cikijing Hamlet and SDN 5 Sindangsari which is in Cijaringao Hamlet. The purpose of this program is to form a culture of reading and understanding reading within the school community of SDN 3 Sindangsari and SDN 5 Sindangsari, as well as improving students' language skills. This research uses a Research Seminar design/method. Seminar research is research conducted by teachers and students from Umtas Thematic KKN by providing training to students which aims to improve the quality (quality) of learning in their class through a certain action in a learning stage. In conclusion, the School Literacy Movement is more than just reading and writing but includes thinking skills according to the stages and components of literacy. Whereas in good practice it is necessary to emphasize the principles of the school literacy movement. In order for schools to be at the forefront of literacy culture, it is necessary to use several implementation strategies. This activity is carried out to foster student interest in reading so that knowledge can be mastered wel